PENERAPAN LAYANAN KONSELING KELOMPOK DENGAN TEKNIK MODELING LANGSUNG DALAM MENINGKATKAN FREKUENSI KEHADIRAN SISWA - Wiwi Indah Sari (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Andi Matappa Pangkep, 2017)
The purpose of this study aimed to determine the effect of the application of group counseling with direct modeling techniques to help students who have low attendance at junior high frequencies. State 2 Bungoro Pangkep. The study population were students of class IX as many as 70 people with a sample of 13 people. Data collection techniques used the questionnaire. Results prior to implementation of group counseling with direct modeling techniques the number of students who have a very low frequency of attendance total of 7 people or 53% categorized as High. Meanwhile, after execution of group counseling with direct modeling techniques the number of students who have low attendance frequency decreased to 3 people or 23% or categorized as very low. Means the group counseling with direct modeling techniques can increase the frequency of student attendance.